2014
DOI: 10.1016/j.intell.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between working memory and intelligence in children: Is the scoring procedure important?

Abstract: Different procedures have been proposed for scoring working memory (WM) tasks. The Absolute Credit Score (ACS) only considers performance in perfectly recalled trials, while the Partial Credit Score (PCS) considers imperfectly recalled ones too. Research indicates that different relationships between WM and general intelligence (the g-factor) may emerge using the ACS or the PCS. We reanalyzed the ACS and PCS obtained in a sample of 176 children in the 4 th and 5 th grades, and found that the PCS strengthened t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 50 publications
(61 reference statements)
1
22
0
Order By: Relevance
“…(). Several tasks included in the battery have been used in other studies (e.g., Caviola et al ., ; Giofrè & Mammarella, ; Giofrè, Mammarella, Ronconi, & Cornoldi, ; Giofrè, Mammarella, et al ., ; Mammarella, Hill, Devine, Caviola, & Szűcs, ; Passolunghi & Mammarella, , ) and revealed good psychometric properties. All tasks were of increasing difficulty.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…(). Several tasks included in the battery have been used in other studies (e.g., Caviola et al ., ; Giofrè & Mammarella, ; Giofrè, Mammarella, Ronconi, & Cornoldi, ; Giofrè, Mammarella, et al ., ; Mammarella, Hill, Devine, Caviola, & Szűcs, ; Passolunghi & Mammarella, , ) and revealed good psychometric properties. All tasks were of increasing difficulty.…”
Section: Methodsmentioning
confidence: 98%
“…All tasks were of increasing difficulty. As for the scoring, we used the partial credit score, expressing the mean proportion of elements within an item that were recalled correctly, as this approach was shown to be more reliable and to increase the predictive validity of WM tasks (see Conway et al ., ), particularly the visuospatial ones (Giofrè & Mammarella, ).…”
Section: Methodsmentioning
confidence: 99%
“…The size judgment task was scored in two ways using an all or none method and a partial credit method. Previous comparisons between these scoring systems has shown that partial credit scoring generally demonstrates more sensitivity and shows higher correlations to other variables of interest (Conway et al, 2005; Friedman & Miyake, 2005; Giofrè, & Mammarella, 2014; St. Clair-Thompson, & Sykes, 2010). Greatest list length, an all or none method used by Montgomery (2000a, 2000b), awarded children credit for the highest list length in which two of the three lists had all the items recalled, and in the correct reorder.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of each set of sentences, immediately after saying whether the statement was true or false, participants were asked to recall the final word in each of the sentences (in their order of presentation), and to be careful to avoid naming non-final words. The proportion of accurately recalled words was computed (i.e., the partial credit score, see Conway, et al, 2005;Giofrè & Mammarella, 2014).…”
Section: Screeningmentioning
confidence: 99%